2011
DOI: 10.1148/radiol.11102413
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Benign and Malignant Breast Lesions by Using Shutter-Speed Dynamic Contrast-enhanced MR Imaging

Abstract: Purpose:To assess the accuracy of the shutter-speed approach compared with standard approach dynamic contrast materialenhanced magnetic resonance (MR) imaging pharmacokinetic analysis for breast cancer diagnosis. Materials and Methods:This study was approved by the institutional review board and was HIPAA compliant. Informed consent was obtained from 89 high-risk women (age range, 28-83 years) who had 92 suspicious lesions with negative fi ndings at mammography (but visible at MR imaging). Each underwent a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(116 citation statements)
references
References 41 publications
19
97
0
Order By: Relevance
“…Our study evaluated effects of post-contrast timing only on select semi-quantitative kinetics features; timing effects may be more significant for other diagnostic variables such as quantitative metrics obtained by DCE-MRI pharmacokinetics analysis. More advanced DCE-MRI approaches to improve diagnostic performance for evaluating breast lesions are an area of active research (21), and recent results have shown promise for achieving accurate pharmacokinetic modeling with shortened acquisitions (22). Further, distinction of benign and malignant lesions is primarily dependent on morphological characteristics (5), which our study did not evaluate as these features are typically assessed in the early dynamic phase within 2 minutes after contrast injection and therefore not impacted by choice of delayed phase scan timing.…”
Section: Discussionmentioning
confidence: 99%
“…Our study evaluated effects of post-contrast timing only on select semi-quantitative kinetics features; timing effects may be more significant for other diagnostic variables such as quantitative metrics obtained by DCE-MRI pharmacokinetics analysis. More advanced DCE-MRI approaches to improve diagnostic performance for evaluating breast lesions are an area of active research (21), and recent results have shown promise for achieving accurate pharmacokinetic modeling with shortened acquisitions (22). Further, distinction of benign and malignant lesions is primarily dependent on morphological characteristics (5), which our study did not evaluate as these features are typically assessed in the early dynamic phase within 2 minutes after contrast injection and therefore not impacted by choice of delayed phase scan timing.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used to monitor neovascularization of tumors and this can be further quantified using pharmacokinetic modeling of tracer distributions 2830. In the past, the specificity of DCE-MRI ranged from 37%–91% 31,32.…”
Section: Detection Of Breast Cancer By Mri/mrsmentioning
confidence: 99%
“…If a one-compartment model fits the data well there may be no case for using a more complex model; however, in vascular tumours measured at high temporal resolution a poor fit is likely as a onecompartment model may not model the vascular component [75]. More elaborate PK models may improve evaluation of dynamic data and better characterise physiological parameters and biological effects [76][77][78][79][80][81][82][83][84], but are not yet supported by sufficient evidence to warrant use as primary endpoints.…”
Section: Recommendations On Analysis • the Analysis Plan Should Be Prmentioning
confidence: 99%